2009
DOI: 10.1136/sti.2009.038778
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis screening among female sex workers in Bangalore, India: comparison of point-of-care testing and traditional serological approaches

Abstract: The Syphicheck-WB test utilising finger-prick whole blood has a relatively low sensitivity in detecting active syphilis. However, among hard-to-reach populations who may not return for follow-up treatment, POC screening with this assay could still confer an advantage over offsite RPR testing with respect to treatment coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 11 publications
2
32
1
Order By: Relevance
“…The point-of-care test can also increase the likelihood of appropriate syphilis treatment. A study at Bangalore, India, showed that the sex workers treated for active syphilis (with reactive RPR and positive Treponema pallidum haemagglutination assay) after a positive on-site pointof-care test was 68.3%, as compared to 44.8% in the control group whose serum samples were collected for off-site RPR testing [10].…”
Section: Discussionmentioning
confidence: 99%
“…The point-of-care test can also increase the likelihood of appropriate syphilis treatment. A study at Bangalore, India, showed that the sex workers treated for active syphilis (with reactive RPR and positive Treponema pallidum haemagglutination assay) after a positive on-site pointof-care test was 68.3%, as compared to 44.8% in the control group whose serum samples were collected for off-site RPR testing [10].…”
Section: Discussionmentioning
confidence: 99%
“…The Syphcheck-WB test using finger prick whole blood was evaluated for detection of active syphilis among female sex workers in Bangalore, India. Compared with the reference RPR and TPHA, the sensitivity and specificity of the POC syphilis were 70.8% and 97.8%, respectively (Mishra et al, 2010). Besides its lower sensitivity, this study revealed that the use of POC screening conferred an advantage over offsite RPR testing among hard-to-reach populations, who may not return for their test results and follow-up treatment.…”
Section: Treponema Specific Rapid Diagnostic Test (Point Of Care -Poc)mentioning
confidence: 93%
“…Besides its lower sensitivity, this study revealed that the use of POC screening conferred an advantage over offsite RPR testing among hard-to-reach populations, who may not return for their test results and follow-up treatment. The proportion of women with active syphilis who were appropriately treated rose from 44.8% to 68.3% (p=0.003) with the use of POC syphilis screening (Mishra et al, 2010). The limitation of rapid syphilis tests is that they cannot distinguish active and treated syphilis; positive results need confirmation with quantitative nontreponemal testing to determine recent infection and response to therapy.…”
Section: Treponema Specific Rapid Diagnostic Test (Point Of Care -Poc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the tests previously described, POC tests require minimal equipment and training and can be performed using microliters of whole blood (generally from a fingerstick) as well as serum or plasma, and the results can be visualized within minutes. A WHO study commissioned to compare the sensitivity and specificity for syphilis of eight point-of care tests with TPPA and TPHA as reference standards reported sensitivities ranging between 84.5 and 97.7% and specificities of 92 to 98% (178), although lower sensitivity was found for whole blood than for the serum or plasma fractions and when tests were performed in the field rather than in the laboratory (179)(180)(181). Despite their lower specificity compared to standard treponemal tests, the use of POC tests will confer an advantage over standard tests for hard-to-reach populations and where lab facilities are not available.…”
Section: Serological Testsmentioning
confidence: 99%